Analiza Drgań Samowzbudnych Wirnika o Dwóch Stopniach Swobody - Muszyńska, A. (Engineering Transactions, 1973)
In the paper stationary, self-excited vibrations of rotor with two degrees of freedom, excited by the action of internal friction within the material of the rotor are analyzed. The characteristics of elasticity and internal friction are assumed to be non-linear and given by Eqs. (2.1). Existence and stability of stationary self-excited vibrations are analyzed as functions of the characteristics (2.1), of internal friction and of the rotational velocity of the rotor. The results obtained may serve to decide whether the rheological model assumed is correct, and to qualitative identification of the internal friction characteristics.